Designing Highly Efficient and Long‐Term Durable Electrocatalyst for Oxygen Evolution by Coupling B and P into Amorphous Porous NiFe‐Based Material. Issue 28 (30th May 2019) - Hu, Fei; Wang, Haiyun; Zhang, Yan; Shen, Xiaochen; Zhang, Guanghui; Pan, Yanbo; Miller, Jeffrey T.; Wang, Kun; Zhu, Shengli; Yang, Xianjin; Wang, Chengming; Wu, Xiaojun; et al.
Abstract: Oxygen evolution reaction (OER) is of great significance for hydrogen production via water electrolysis, which, however, demands development of highly active, durable, and cost‐effective electrocatalysts in order to stride into a renewable energy era. Herein, highly efficient and long‐term durable OER by coupling B and P into an amorphous porous NiFe‐based electrocatalyst is reported, which possesses an amorphous porous metallic bulk structure and high corrosion resistance, and overcomes the issues associated with currently used catalyst nanomaterials. The PB codoping in the activated NiFePB (a‐NiFePB) delocalizes both Fe and Ni at Fermi energy level and enhances p–d hybridization as simulated by density functional theory calculations. The harmonized electronic structure and unique porous framework of the a‐NiFePB consequently improve the OER activity. The activated NiFePB thus exhibits an extraordinarily low overpotential of 197 mV for harvesting 10 mA cm −2 OER current density and 233 mV for reaching 100 mA cm −2 under chronopotentiometry condition, with the Tafel slope harmoniously conforming to 34 mV dec −1 . Impressive long‐term stability of this new catalyst is evidenced by only limited activity decay after 1400 h operation at 100 mA cm −2 . This work strategically directs a way for heading up a promising energy conversion alternative. Abstract : Highly efficient and long‐term durable oxygen evolution reaction (OER) is achieved by coupling B and P into an amorphous porous NiFe‐based electrocatalyst. The PB codoping in NiFePB delocalizes both Fe and Ni at Fermi energy level and enhances p–d hybridization so that NiFePB exhibits an extraordinarily low overpotential of 197 mV for harvesting 10 mA cm −2 OER current density.